Alzheimer’s Amyloid-β Accelerates Human Neuronal Cell Senescence Which Could Be Rescued by Sirtuin-1 and Aspirin - Li, Yi; Lu, Juan; Hou, Yujun; Huang, Shichao; Pei, Gang (Frontiers in Cellular Neuroscience, 2022)
Cellular senescence is a major biological process related to aging. Neuronal cell senescence contributes to the pathogenesis of many aging-related neurodegenerative diseases including Alzheimer’s disease (AD). In this study, we showed that amyloid-β42 oligomers (Aβ), one of the core pathological players of AD, significantly up-regulated the expression of senescence markers, p21, plasminogen activator inhibitor-1 (PAI-1), and SA-β-gal (senescence-associated β-galactosidase) in multiple human neuronal cells, including SK-N-SH cells, SH-SY5Y cells, and neural stem cell (NSC)-derived neuronal cells. Moreover, it was consistently observed among the cells that Aβ promoted senescence-associated DNA damage as the levels of 8-OHdG staining, histone variant γH2AX phosphorylation, and genomic DNA lesion increased. Mechanism study revealed that the exposure of Aβ markedly suppressed the expression of sirtuin-1 (SIRT1), a critical regulator of aging, and the exogenous expression of SIRT1 alleviated Aβ-induced cell senescence phenotypes. To our surprise, a widely used cardiovascular drug aspirin considerably rescued Aβ-induced cellular senescence at least partially through its regulation of SIRT1. In conclusion, our findings clearly demonstrate that exposure of Aβ alone is sufficient to accelerate the senescence of human neuronal cells through the down-regulation of SIRT1.